An explicit formula based estimation method for distribution network reliability - Xiang, Yue; Su, Yunche; Wang, Yang; Liu, Junyong; Zhang, Xin (IEEE, 2019)
An improved explicit estimation algorithm is proposed for reliability estimation of distribution network. Firstly, hierarchical clustering is used to identify and cluster typical feeders based on topology structure. Secondly, the explicit formula of reliability indices under each typical feeder topology is derived by regression analysis, to establish the model for network reliability estimation. Numerical simulations show the suitability of the proposed method in obtaining accurate reliability index for diversified network topology.
Keywords: reliability evaluation; explicit estimation; hierarchical clustering; distribution network planning